Substance P in ovarian carcinoid. Issue 2 (February 1980) - Skrabanek, P; Dervan, P; Cannon, D; Powell, D
Abstract : A high content of substance P (124 ng/g wet tissue) was demonstrated by radioimmunoassay in lymph node metastases in a patient with bilateral ovarian carcinoid tumours. The plasma substance P level was elevated but urinary 5-hydroxyindoleacetic acid (5-HIAA) was low. It is suggested that, in some carcinoid patients, an elevated plasma substance P level may help diagnosis and follow-up when urinary 5-HIAA is normal.